2023
DOI: 10.3390/pathogens12080984
|View full text |Cite
|
Sign up to set email alerts
|

HPV and Other Risk Factors Involved in Pharyngeal Neoplasm—Clinical and Morphopathological Correlations in the Southwestern Region of Romania

Abstract: Oropharyngeal squamous cell carcinoma (OPSCC) development is strongly associated with risk factors like smoking, chronic alcohol consumption, and the living environment, but also chronic human papilloma virus (HPV) infection, which can trigger cascade cellular changes leading to a neoplastic transformation. The prevalence of these factors differs among different world regions, and the prevention, diagnosis, and prognosis of OPSCC are highly dependent on them. We performed a retrospective study on 406 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Oropharyngeal cancer (OPC) is a malignancy that affects the oral cavity and pharyngeal region [ 1 ]. In recent decades, research has revealed a significant association between human papillomavirus (HPV) infection and the development of oropharyngeal cancer [ 2 , 3 , 4 ]. HPV represents a family of sexually transmitted viruses that affect the epithelia of the mucosa and skin [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Oropharyngeal cancer (OPC) is a malignancy that affects the oral cavity and pharyngeal region [ 1 ]. In recent decades, research has revealed a significant association between human papillomavirus (HPV) infection and the development of oropharyngeal cancer [ 2 , 3 , 4 ]. HPV represents a family of sexually transmitted viruses that affect the epithelia of the mucosa and skin [ 5 ].…”
Section: Introductionmentioning
confidence: 99%